Full Non-Rigid Group Theory for Hexamethylethane - Reza Darafsheh, Mohammad; Moghani, Ali (Asian Journal of Chemistry, 2010)
The non-rigid molecule group theory in which the dynamical symmetry operations are defined as physical operations is applied to deduce the character table of the full non-rigid molecule group (f-NRG) of hexamethylethane. The f-NRG of this molecule is seen to be isomorphic to the group (Z3 × Z3 × Z3 × Z3 × Z3 × Z3) Λ G12 of order 8748 which has 174 conjugacy classes. Here (Z3 × Z3 × Z3 × Z3 × Z3 × Z3) Λ G12 denotes the semi direct product of the direct products of 6 copies of the cyclic group Z3 by the dihedral group of order 12. Using some results in finite group theory and GAP system, we find the complex character table of this group.